2013
DOI: 10.4236/ajps.2013.48197
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Accumulation and Nutrient Uptake of Jerusalem Artichoke (<i>Helianthus tuberosus</i> L.)

Abstract: The dynamics of biomass accumulation during the growing period, the yield of leafy stalks and tubers, and the nutrient concentration and nutrient uptake of the yield were investigated for two Jerusalem artichoke varieties (Tápiói Korai and Tápiói Sima) in a field experiment involving mineral fertilisation. Considerable differences were observed between the dynamics of leafy stalk and tuber development in Tápiói Korai which has a short vegetation period and Tápiói Sima where the vegetation period is long. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Due to high regeneration capacity of JA tops, it can be cut 3-4 times a year (Izsáki and Kádi, 2013). The aerial part of JA is characterized by its high yield (a fresh and dry matter [DM] yields of over 120 and 30 t/ha, respectively) and high nutritional value (Kays and Nottingham, 2008;Diederichsen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high regeneration capacity of JA tops, it can be cut 3-4 times a year (Izsáki and Kádi, 2013). The aerial part of JA is characterized by its high yield (a fresh and dry matter [DM] yields of over 120 and 30 t/ha, respectively) and high nutritional value (Kays and Nottingham, 2008;Diederichsen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental and economic performance assessed in the current study was based on yield data from one year. The data used, however, are comparable to field trials with similar tuber crops such as Jerusalem artichoke, which demonstrated that an increase in nitrogen fertilization leads to an increase in tuber yields [53,54], even though there is more information needed as annual climatic effects, such as changes in precipitation, can have a significant impact on yacon tuber yield formation [6].…”
Section: Guidelines For An Economically and Environmentally Sustainabmentioning
confidence: 95%
“…Variability of the soil and weather environment significantly modified the level of all the macronutrients in the aboveground parts. According to Seiler (1988), Harmankaya et al (2012), Izsáki and Kádi (2013) diversity of the environment in which Jerusalem artichoke grows modifies the processes of internal regulation. Therefore, variability may occur within the plant, the main stem and lateral shoots and it may be linked to the years and place of cultivation.…”
Section: Resultsmentioning
confidence: 99%